AYUSHMAN BHARAT- AN INITIATIVE TOWARDS CREATION OF HEALTHY INDIA: AN EMPIRICAL ANALYSIS - A, KhalidaKhanum; S, Nagaraja; S, Devarajappa (International Journal of Psychosocial Rehabilitation, 2020)
Ayushman Bharat is a central government sponsored health scheme in India, launched on 23th Sept.2018, under the patronage of Ministry of Health and Family Welfare. The main motive of the scheme is to provide primary, secondary and tertiary health coverage to economically backward people i.e. for BPL card holders. The present paper is based on empirical study conducted in Tumkur district of Karnataka state consisting of 89 beneficiaries out of 100samples selected for the study. Data collected from beneficiaries about their satisfaction level regarding coverage of illness, availability of facilities, procedure of availing benefits, cashless settlement at the time of hospitalization and experience of any problem during hospitalization such as unexpected billing, transparency problem and related to quality of medicine. The results found that majority of beneficiaries depend upon public health sector as their financial condition does not permit them to afford medical facilities from private hospitals. As a result majority of them demand changes in the scheme through the provision of better health facilities in government hospitals itself.